2014
DOI: 10.1113/jphysiol.2014.279240
|View full text |Cite
|
Sign up to set email alerts
|

Healthy humans with a narrow upper airway maintain patency during quiet breathing by dilating the airway during inspiration

Abstract: Key pointsr During quiet breathing, the muscles of the upper airway of healthy humans contract to dilate the airway during inspiration.r We used dynamic tagged magnetic resonance imaging to show that the amount of active upper airway dilatation during inspiration increases as airway cross-sectional area decreases.r Older and more overweight subjects have smaller airways, and this is linked to increased active airway dilatation.r These data show that healthy subjects with narrow airways can overcome anatomical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 39 publications
0
30
1
Order By: Relevance
“…A larger study of people without OSA has shown that inspiratory dilatation was larger with increasing BMI (Cheng et al . ). Also in contrast with our results, Brown et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A larger study of people without OSA has shown that inspiratory dilatation was larger with increasing BMI (Cheng et al . ). Also in contrast with our results, Brown et al .…”
Section: Discussionmentioning
confidence: 97%
“…In particular, it was found that airway dilatation during inspiration is larger in the presence of a narrow airway in healthy individuals (Cheng et al . ), differs between heathy controls and people with OSA, but differs between people with and without OSA and varies with OSA severity (Brown et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In healthy humans, the combined phasic inspiratory and tonic components represent less than 2% of maximal spontaneous GG activity (247). Humans who do not meet the clinical criteria for OSA despite having smaller than normal upper airway cross-sectional area produce larger anterior movements of the tongue during inspiration than other control subjects (90). This suggests that, at least in humans studied during wakefulness, a subclinical reduction of upper airway patency elicits a compensatory activation of upper airway dilating muscles during inspiration.…”
Section: Upper Airway Muscles and Their Activity Patternsmentioning
confidence: 99%
“…Indeed, in light of recent findings [33,34], morbidly obese individuals who do not have OSA likely have "supranormal" neuromuscular compensatory mechanisms that protect them from OSA. This concept is further supported by >50% of the study participants having a passive Pcrit above −2 cmH 2 O and elevated AHIs during REM sleep into the pathogenic range when neuromuscular compensatory mechanisms are reduced or absent.…”
Section: @Erspublicationsmentioning
confidence: 99%